MEDIATION AS AN ALTERNATIVE METHOD OF RESOLUTION OF LEGAL CONFLICTS - Богатюк, Ірина Григорівна; Базь, Анастасія Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to highlight issues related to the use of mediation as an alternative way of resolving legal conflicts. Methods of research: applied a set of philosophical, general scientific, historical and special scientific principles and methods of cognition. Results: mediation requires scientific justification and practical implementation in the activities of the persons engaged in it. The high level of effectiveness of the phenomenon of mediation is characterized by its basic principles: voluntariness, confidentiality, efficiency. Legislative definitions also require the following: fixing the list of cases in which mediation can be appointed; regulation of the requirements for the mediators themselves and the procedure for their selection; definition of specific principles and forms of mediation, as well as conditions for receiving mediators information on the case and important procedural issues. Important and useful assistance in the process of introducing mediation into its practical use by Ukrainian society is the experience of foreign countries, in particular European countries. Discussion: there are a number of ways in the world that provide reconciliation to parties to a contentious legal relationship without the direct involvement of a court. And, first of all, they need to be thoroughly investigated and predict the possible advantages and disadvantages, which will result in granting them the status of a legal or procedural institute in Ukraine. At present, unfortunately, this issue in our country is poorly researched and there is only a limited number of specialists who are real experts in this field. The development of alternative ways of resolving legal conflicts is gaining popularity and is increasingly used in Ukraine. Undoubtedly, the out-of-court resolution of disputes cannot completely replace the judiciary, but at the same time can help to some extent reduce the burden on the courts, which often do not handle so many cases. In addition, certain ways of resolving conflicts do not prohibit the parties from using those methods that will be most appropriate for the settlement of the dispute and will meet the interests and requirements of the parties. Despite the shortcomings, in particular the lack of framework legislation to regulate the mediation process, much has already been done to implement it.